2019
DOI: 10.1111/jop.12945
|View full text |Cite
|
Sign up to set email alerts
|

Role of the arecoline/YAP1/BMP4 pathway in promoting endothelial‐mesenchymal transition in oral submucous fibrosis

Abstract: Background Oral submucous fibrosis (OSF) is a potentially malignant lesion characterized by epithelial‐mesenchymal transition (EMT). Bone morphogenetic protein 4 (BMP4) promotes EMT in fibrotic diseases, but the underlying mechanisms and its potential role in OSF are unclear. This study investigates whether BMP4 plays a role in the pathogenesis of OSF and explores the underlying mechanisms. Methods The expression of BMP4 and the EMT proteins E‐cadherin and vimentin was investigated in OSF specimens by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Studies have pointed out that EMT signaling pathway is an important mechanism for the development of ovarian tumor [5,29]. Studies have shown that the BMP4-mediated signaling pathway led to morphological changes in tumor cells and enhanced cell adhesion, migration, and invasion by inducing EMT [30]. The EGFR signaling pathway inhibits the expression of miR-125a through the transcription factor PEA3, thereby promoting EMT and leading the poor prognosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have pointed out that EMT signaling pathway is an important mechanism for the development of ovarian tumor [5,29]. Studies have shown that the BMP4-mediated signaling pathway led to morphological changes in tumor cells and enhanced cell adhesion, migration, and invasion by inducing EMT [30]. The EGFR signaling pathway inhibits the expression of miR-125a through the transcription factor PEA3, thereby promoting EMT and leading the poor prognosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently research investigated the potential pharmacological and toxic effects of arecoline [26,27]. The main toxic effects of arecoline are oral submucous fibrosis (OSF), oral squamous cell carcinoma (OSCC) and genotoxicity [28][29][30]. Cefamandole has been recommended in empiric therapy for patients with community-acquired pneumonia and as a prophylactic agent for patients receiving various surgical procedures [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, AN-induced EMT has been studied in cancer progression, rather than in normal physiological processes. Arecoline, the component of AN-extract, can induce EMT, thereby exacerbating cancer progression (Zheng et al, 2018;Chang et al, 2019;Yao et al, 2019). Thus, AN-induced EMT is implicated in the primary mechanisms by which epithelial cancer cells acquire malignant phenotypes that promote metastasis.…”
Section: Discussionmentioning
confidence: 99%